Automating Processes of Personnel Motivation Management in the Context of Implementing a Principle of Social Justice - I. A. Ivanova; O. S. Osipova; V. N. Pulyaeva (Управленческие науки, 2020)
The paper is devoted to studying the experience of Russian organizations in solving the problem of automation of one of the main HR functions — motivation and work incentives of employees of the organizations. After personnel administration, HR motivation management has become the second HR function, which is successfully automated in Russian organizations. The methodological basis of the study is a modern understanding of the theory of human capital. The research methodology provides for the reconstruction of the labor stimulation process based on the development and implementation of key performance indicators in conjunction with the automation processes of operational HR processes. The work results as follows: systematization of software that automates the basic processes for staff motivation; development of recommendations for HR departments on the development and implementation of an automated system of main performance indicators. The authors have proved that the correctly implemented automation of the HR function to calculate compensation and benefits during the transition to a more complex remuneration system makes it possible in practice not just to increase the economic results of the organization, but also to implement the fundamental principle of effective management — the principle of a fair assessment of the results of each employee’s work.